A new role of neuraminidase (NA) in the influenza virus life cycle: implication for developing NA inhibitors with novel mechanism of action. (8th April 2016) - Yang, Jie; Liu, Shuwen; Du, Lanying; Jiang, Shibo
Summary: The entire life cycle of influenza virus involves viral attachment, entry, replication, and release. Previous studies have demonstrated that neuraminidase (NA) is an essential glycoprotein on the surface of influenza virus and that it is responsible for release of progeny virions from the host cell to infect new cells. However, recent studies have also suggested that NA may play other roles in the early stages of the viral life cycle, that is, viral attachment and entry. This review focuses on the new role of NA in the early stages of influenza life cycle and the corresponding development of novel NA inhibitors. Copyright © 2016 John Wiley & Sons, Ltd.